The Features of English Book Used in 2013 Curriculum at Junior High School Level - Darayani, Nisrin; Masduki, Masduki (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2017)
An Investigation on Team Teaching Implemented by Local and Foreign Teachers in Teaching English at SMAN 1 Ketapang Sampang